¿Relocalización o bienestar social? Evaluación de las condiciones de accesibilidad en erradicaciones del Área Metropolitana de Tucumán - Castañeda Nordmann, Ana Laura; Gómez López, Claudia Fernanda (El Colegio de México A.C., 2019)
The Metropolitan Area of Tucumán (AMeT) is undergoing a process of gentrification linked to intense socio-spatial fragmentation, expressed through the unequal growth – regarding both area and population– of municipalities and communes (Gómez López, Cuozzo and Boldrini, 2015). The Institute for Planning, Housing and Urban Development (IPVDU) is undertaking operations to regularize historic settlements in the ATS through relocations. In this context, this research aims to conduct a critical review of this process, based on a multicriterial, comparative analysis of cases, in relation to the strategies to ensure the accessibility of basic services and quality of life for the population.